Learning Design in Translation Topic with Cinema Context for 9th Grade Students - Rosyada, Amrina; Zulkardi, Zulkardi; Susanti, Ely; Meryansumayeka, Meryansumayeka (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2025)
The use of real-world contexts in RME learning makes the concepts learned by students more meaningful. In this research, a cinema, which is relevant to students' lives are used as learning contexts. This research aims to develop a learning trajectory based on the RME approach using cinema context to help students understand the concept of translation. The research method used in this study is a design research validation study type with 33 ninth-th grade students of SMP Negeri 9 Palembang as subjects. Data collection techniques used include observation data collection techniques, interviews, field notes, and documentation. This study produces a Hypothetical Learning Trajectory (HLT) that can help students understand the translation concept. The resulting HLT includes four activities, namely observing contextual problems in cinemas as a starting point in understanding the concept of translation, identifying the cinema seats position as the initial points to be translated, drawing the cinema layout in cartesian coordinates to find the relationship between the coordinates of the translated point and the initial point, generalizing the shifts of the seat position to discover the concept of translation.